Correlation of Neutrophil to Lymphocyte Ratio with in Hospital Mortality in Patients of Acute Coronary Syndrome - Khan, Ismail Ahmed; Shahzad, Syed Khurram; Chaudhry, Azhar Ali; Khan, Sheharbano Ahmed; Aziz, Zohair; Kiani, Sadaf Shabbir; Toru, Fahad Khan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To study the correlation of Neutrophil to Lymphocyte Ratio (NLR) with in-hospital mortality in patients of Acute Coronary Syndrome (ACS).Study Design: Analytical Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi, Pakistan, from Jul-Dec 2022.Methodology: One hundred and sixty patients regardless of gender and presented with ACS were included in this study. Their venous blood samples were taken, at the time of admission and were analyzed by the CBC analyzer (Mandray BC 6200) at pathology laboratory and who were delineated into high NLR (>5.25) and low NLR (≤5.25) groups. Their in-hospital morbidity and mortality outcomes were noted. Chi-squared test was applied to compare qualitative variables. Independent samples t-test was applied to compare mean values. Receiver Operating Characteristic (ROC) curve of NLR for predicting in-hospital mortality was plotted, and p-value of